Penguatan Sikap Percaya Diri melalui Dreams Book bagi Siswa Kelas I SDN Tegalombo I Kalijambe Sragen - Yan Vita (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2016)
This article aims to explore the reinforcement of confidence through dreams book. In the early condition, the students have low self-confidence. To increase theself-confidence of the students, the teacher begins to explore the dreams of the students and make the students realize their dreams through dreams book. Through qualitative descriptive, this research described how to implement dreams book in the learning process. The teacher asked the students to make simple book consisted of four pages. As the evaluation, the teacher used some assessments, such as observation, self-assessment, and friend assessment. The teacher asked the student to fill out the sheet of self-assessment rubric and friend assessment rubric. For the observation, the teacher made observation rubric. From the result of this evaluation, the teacher concluded that self-confidence of the students showed improvement. As much as 34% and 36% of students obtain score 3 and 4, respectively. Therefore, the students who get a score above the KKM (Kriteria Ketuntasan Minimal) is 80%. It means that the score in every indicator of self-confidence showed improvement.Keywords: Self-confidence, dreams book